Industrial wastewater treatment in Latin America and Europe: methods and applications. a systematic review of the literature - Hidalgo Salhuana, Gianfranco Julinho (2024)
This research seeks to disseminate the different methods for wastewater treatment in different industries in Latin America and Europe, as well as the most used ones. According to the literature reviewed, a large percentage of industrial wastewater is not treated, especially in Latin America, causing a negative impact on the ecosystem. There are different methods for the treatment of industrial wastewater; however, most of the research on industrial wastewater treatment focuses on the study of a single treatment method. The methodology used was the systematic literature review, 5 categories and 10 subcategories of study were formed to analyze 30 articles published between 2015 and 2020. As the main result, it was obtained that green technologies, such as the wetlands method and use of microalgae, were the most studied in the last five years. The main limitation of this study was the lack of information regarding industrial sectors other than textile and food, so it is suggested to do future research focusing on sectors not yet studied, such as automotive, metalworking, agro-industrial, among others.